If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 = (3x) + (42x) Combine like terms: (3x) + (42x) = 45x 52 = 45x Solving 52 = 45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45x' to each side of the equation. 52 + -45x = 45x + -45x Combine like terms: 45x + -45x = 0 52 + -45x = 0 Add '-52' to each side of the equation. 52 + -52 + -45x = 0 + -52 Combine like terms: 52 + -52 = 0 0 + -45x = 0 + -52 -45x = 0 + -52 Combine like terms: 0 + -52 = -52 -45x = -52 Divide each side by '-45'. x = 1.155555556 Simplifying x = 1.155555556
| Y+x=325 | | n=687/24(-15) | | x^7=64x^5 | | Y-x=325 | | 3x-8=7-2x | | c/5.3+8.3=11.3 | | m+8=2 | | 2x^2+5=x^2-5x-1 | | 7d=-28 | | 23y=-92 | | -12x+35=0 | | Y=325-x | | 5+2x=65 | | 23y=-28 | | 7x+9-3x=-11 | | x+-5=4 | | 50=1.5x^2 | | 3(5-3z)=0 | | 11t=-7 | | t^2-t=72 | | z/20=-1 | | 2x+7y-32=0 | | 0.5(8n-2)=-(-8+9n)-5n | | 2.8+-5= | | -5x=90 | | -6x+16=-48 | | 6(x-3)-9(x-1)=5-(x+3) | | v/3=-6 | | -3(1+14x)+13x=-3(1-12x) | | 5(y-1)=2Y+4 | | 3x+2(x+400)=2900 | | 2-1/4=7/8 |